A NONPARAMETRIC SYSTEM IDENTIFICATION BASED ON TRANSIENT ANALYSIS WITH PLANT PROCESS OF HEAT EXCHANGER AS STUDY CASE - Tatang Mulyana (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2015)
In this article, a nonparametric identification system based on transient analysis has been reviewed, by taking the case in some of the data plant process of heat exchanger. Results of the study found that the first-order transfer function without time-delay the proposed model to the data with a temperature constant value is 35.20 ºC and the time constant is 7200 seconds. This model has been fit to meet the existing data proving that the results of the calculation error do not exceed 2%